2007
DOI: 10.1523/jneurosci.3974-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Ribbon Synapses in Hair Cells Is Driven by Thyroid Hormone

Abstract: Ribbon synapses of inner hair cells (IHCsϪ/Ϫ mice maintained the normally temporary efferent innervation. Moreover, they lacked large-conductance Ca 2ϩ -activated K ϩ channels and KCNQ4 channels. This together with the persistently increased Ca 2ϩ influx permitted continued action potential generation. We conclude that TH regulates IHC differentiation and is essential for morphological and functional maturation of their ribbon synapses. We suggest that presynaptic dysfunction of IHCs is a mechanism in congenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 74 publications
9
108
1
2
Order By: Relevance
“…This dif- ference was caused by the lack of I K,f expression in Pax8 Ϫ/Ϫ IHCs at P12 or later, as confirmed by analysis of K ϩ current activation time constants and immunohistochemistry (data not shown) (Sendin et al, 2007), similar to our findings for IHCs of hypothyroid rats.…”
Section: Neonatal Spiking Activity and Ca 2؉ And K ؉ Currents In Athysupporting
confidence: 88%
See 3 more Smart Citations
“…This dif- ference was caused by the lack of I K,f expression in Pax8 Ϫ/Ϫ IHCs at P12 or later, as confirmed by analysis of K ϩ current activation time constants and immunohistochemistry (data not shown) (Sendin et al, 2007), similar to our findings for IHCs of hypothyroid rats.…”
Section: Neonatal Spiking Activity and Ca 2؉ And K ؉ Currents In Athysupporting
confidence: 88%
“…The reduced exocytosis efficiency (P13-P18) (Fig. 9D) (Sendin et al, 2007) and the lack of maturation of presynaptic proteins in IHCs of Pax8 Ϫ/Ϫ compared with control mice (Sendin et al, 2007) is in line with this conclusion. Given that in hypothyroid rat IHCs the presynaptic machinery stays similarly immature, the reduced exocytosis efficiency would alone impair hearing thresholds at an age of 4 weeks when Ca 2ϩ currents reach the low amplitudes of control IHCs.…”
Section: Direct and Indirect Effects Of Thsupporting
confidence: 70%
See 2 more Smart Citations
“…Thus, contrary to the cessation of ACh sensitivity normally seen in wild-type mice at around P13-14 (Katz et al 2004), it persists up to 6 weeks after birth in Ca v1.3 knockout mice (Brandt et al 2003;Nemzou et al 2006). Moreover, during this critical developmental window, several studies have shown that modifications in the expression of proteins involved in thyroid hormone signaling alter IHC spiking activity, probably due to the lack of expression of BK and KCNQ4 channels together with an increase in calcium influx Brandt et al 2007;Sendin et al 2007). These data indicate that there is a concerted regulation of the functional expression of ion channels during IHC maturation.…”
Section: Discussionmentioning
confidence: 99%